Evolution - Barton, Nicholas H.; Barton, Nicholas H.; Briggs, Derek E. G.; Eisen, Jonathan A.; Goldstein, David B.; Patel, Nipam H. (New York, Cold Spring Harbor Laboratory Press, 2007)
Evolutionis a new book on evolutionary biology that integrates molecular biology, genomics, and human genetics with traditional studies of evolutionary processes. Recommended as a primary textbook for undergraduate courses in evolution Required reading for biologists seeking a clear, current, and comprehensive account of evolutionary theory and mechanisms Written by experts in population genetics, bacterial genomics, paleontology, human genetics, and developmental biology Integrates molecular and evolutionary biology in ways that reflect current directions in research Contents and CoverageThis extensively illustrated, full-color book has four sections: Introduction(Part I) gives an account of how the ideas underpinning evolutionary theory developed and a history of experiments and ideas in the development of molecular biology. Origin and Diversification of Life(Part II) describes the history of life on earth from the origin of life to the evolution of humans, with emphasis on the major transitions in genetic organization and novel adaptations that have appeared. The diversity of life is emphasized. The chapters make extensive use of information from complete genome sequences and analysis of molecular mechanisms in development. Evolutionary Processes(Part III) describes how the diversity of life is generated: How variation arises and how selection acts are considered in detail. Many examples used to illustrate these processes are drawn from molecular sources. Human Evolution(Part IV) discusses human evolution and diversity. The benefits of molecular markers for our understanding of human evolution are highlighted and these findings integrated with paleontological evidence. Also discussed is the use of evolutionary methods to identify genetic differences that predispose people to specific diseases and affect their responses to treatment. Online-only ChaptersAdditional chapters, found on the Web only, deal with techniques and models used in studying evolutionary biology, emphasizing the contribution of molecular biology and genomics to phylogenetic reconstruction methods. Resources for InstructorsThe EvolutionWeb site (www.evolution-textbook.org)is an invaluable supplement to the textbook, a resource for teachers that will contain downloadable figures (for PowerPoint or overhead display) and chapter problems. Request exam copies and other informationVisit the EvolutionWeb site now for more information about this new book. Request a detailed Table of Contents, Sample Chapters, Exam Copies, and Updates about Evolution.
Includes bibliographical references.; Glossary 783-801p.; Index 811-833p.
Keywords: Biology; Evolution